Pendidikan Agama Sebagai Komponen Dasar Dalam Pembentukan Manusia Yang Berkualitas - Khoirunnisaa Khoirunnisaa (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2017)
The totality of humanity, idealism and faith is the educational product expected for national and state survival. Religious education in schools is a strategic arena of nation building. Healthy human beings physically and mentally, responsible, independent, noble, personality, discipline and hardworking and tough, will develop, if learners get a religious education enough. So the religious education also has an important position. If religious education is good, then it is certain to be printed human quality devoted to religion and the country with the rules of values and good norms